DAMPAK PAJAK DIGITAL TERHADAP PERILAKU WAJIB PAJAK ORANG PRIBADI DALAM EKOSISTEM E-COMMERCE INDONESIA - Kamil, Islamiah; Yolifiandri, Yolifiandri (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This study aims to analyze the impact of digital tax implementation on the behavior of individual taxpayers transacting in Indonesia's e-commerce ecosystem. Digital tax is a policy implemented to regulate and increase state revenue from the digital economy sector, but its implementation can influence consumer behavior in conducting online transactions. This research uses a quantitative method with a survey approach involving 200 respondents who actively transact on various e-commerce platforms, such as Tokopedia, Shopee, Lazada, and Bukalapak. The collected data were analyzed using linear regression methods to measure the relationship between digital tax and changes in consumer behavior, including purchasing decisions and compliance with tax obligations. The analysis results show that digital tax has a significant impact on purchasing behavior, where respondents reduced transaction frequency due to price increases after tax. On the other hand, respondents demonstrated increased awareness and compliance with tax obligations after the introduction of digital tax. These findings provide insights into the impact of digital tax policies on consumer behavior and tax compliance in the e-commerce sector, as well as the importance of an appropriate approach in implementing this policy.